2018
DOI: 10.1002/uog.17544
|View full text |Cite
|
Sign up to set email alerts
|

Small‐for‐gestational‐age babies after 37 weeks: impact study of risk‐stratification protocol

Abstract: The findings of this study suggest that protocol-based management of SGA babies may improve outcome, and that identification of moderate SGA should not in isolation prompt delivery. Larger numbers are required to assess any impact on perinatal mortality. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 37 publications
(42 reference statements)
0
37
0
1
Order By: Relevance
“…Interestingly, a study comparing routine induction at 37 weeks for all SGA detected cases with selective induction only for those classified as FGR according to the previously mentioned criteria (EFW <3rd centile, CPR and UtA) showed not only less intervention (cesarean delivery rate of 25% of 143 vs 40% 138; P < .06) but also improved neonatal outcomes (composite neonatal morbidity of 9% vs 22%; P < .01). 94 In this series, the qualifying criteria for FGR were EFW <3rd centile in 35.9% (101/ 281), an abnormal uterine Doppler velocimetry in 31% (29/93), an abnormal CPR in 19.6% (55/281), and first-trimester low pregnancy-associated plasma protein-A in the remaining 5% (14/281).…”
Section: Doppler Parametersmentioning
confidence: 73%
See 1 more Smart Citation
“…Interestingly, a study comparing routine induction at 37 weeks for all SGA detected cases with selective induction only for those classified as FGR according to the previously mentioned criteria (EFW <3rd centile, CPR and UtA) showed not only less intervention (cesarean delivery rate of 25% of 143 vs 40% 138; P < .06) but also improved neonatal outcomes (composite neonatal morbidity of 9% vs 22%; P < .01). 94 In this series, the qualifying criteria for FGR were EFW <3rd centile in 35.9% (101/ 281), an abnormal uterine Doppler velocimetry in 31% (29/93), an abnormal CPR in 19.6% (55/281), and first-trimester low pregnancy-associated plasma protein-A in the remaining 5% (14/281).…”
Section: Doppler Parametersmentioning
confidence: 73%
“…87 In late SGA fetuses, CPR becomes abnormal in w20% of cases. 5,94 The CPR improves the sensitivity of UA and MCA alone, because it is already decreased when its individual components are still within normal ranges. 87,88 A recent systematic review 90 found that in fetuses with SGA born >32 weeks of gestational age, CPR (9 studies) adds value to assessment over MCA (8 studies) in predicting adverse outcomes.…”
Section: Brain Dopplermentioning
confidence: 99%
“…As SGA is just one manifestation of FGR, even the universal detection of SGA will have limited effects on stillbirth and neonatal morbidity. As some SGA fetuses are constitutionally small, and probably not at increased perinatal risk, iatrogenic delivery may be harmful. It is therefore important to identify other predictors of adverse outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The CPR was expressed as a centile for gestational age according to Baschat–Gembruch charts. Established cut‐offs of EFW, ACGV and CPR were used.…”
Section: Methodsmentioning
confidence: 99%
“…Despite advances in antenatal care, the search for a test to identify the fetus at risk for intrauterine demise continues. The cerebroplacental ratio (CPR), a marker of brain sparing, is emerging as a predictor of adverse perinatal outcome, fetal growth restriction (FGR), neonatal care unit admission, intrapartum fetal compromise, episodes of recurrent reduced fetal movements, postnatal circulatory problems and perinatal death in near-term fetuses [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . Low CPR reflects redistribution of the cardiac output to the brain and has been shown to improve the accuracy of predicting adverse outcome, as compared with middle cerebral artery (MCA) or umbilical artery (UA) Doppler alone [19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%